MANAGING the PROFESSIONAL SERVICE FIRM - Maister, David H., author 332703 (New York : THE FREE PRESS, A Division of Macmillan, Inc. ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
Professional firms differ from other business enterprises in two distinct ways: first, they provide highly customized services and thus cannot apply many of the management principles developed for product-based industries. Second, professional services are highly personalized, involving the skills of individuals. Such firms must therefore compete not only for clients but also for talented professionals. Drawing on more than ten years of research and consulting to these unique and creative companies, David Maister explores issues ranging from marketing and business development to multinational strategies, human resources policies to profit improvement, strategic planning to effective leadership. While these issues can be complex, Maister simplifies them by recognizing that “every professional service firm in the world, regardless of size, specific profession, or country of operation, has the same mission statement: outstanding service to clients, satisfying careers for its people, and financial success for its owners.”